Engaging children and adolescents with acquired brain injury and their families in goal setting: The clinician perspective. Issue 1 (2nd January 2022) - Jenkin, Taylor; Anderson, Vicki; D'Cruz, Kate; Collins, Alana; Muscara, Frank; Scheinberg, Adam; Knight, Sarah
ABSTRACT: This paper explored clinicians' experiences of the goal setting process with children and adolescents with acquired brain injuries (ABI) and their families in paediatric neurorehabilitation. Semi-structured interviews were conducted with 13 clinicians, all members of an interdisciplinary paediatric rehabilitation service, who work with children and adolescents with ABI and their families. Interview transcripts and additional data were analysed using constructivist grounded theory methods. Three main themes and sub-themes were developed: (1) Seeing the bigger picture: Goals change over time ; Families set bigger picture goals ; Need-to-dos: Goals that the child/adolescent needs to achieve ; and Want-to-dos: Goals that the child/adolescent wants to achieve ; (2) Collaborating as a team: Everyone needs to be on the same page ; Hearing the child's/adolescent's voice ; and Parents as advocates ; and (3) Recognizing and navigating challenges: Child-/adolescent- and family-related challenges and Time as a service-related challenge . Participants perceived the clinician's role during goal setting as that of an active collaborator, enabling children and adolescents with ABI and their families to generate meaningful goals. These findings demonstrate insights into goal setting in paediatric ABI neurorehabilitation from clinicians' perspectives, and highlight the importance of collaboration, flexibility and anticipation of challenges in facilitating children's, adolescents' and families' involvement in this process.